Hydrothermal liquefaction of biomass: Developments from batch to continuous process. (February 2015) - Elliott, Douglas C.; Biller, Patrick; Ross, Andrew B.; Schmidt, Andrew J.; Jones, Susanne B.
Highlights: HTL has been evaluated with biomass feedstock ranging from lignocellulosic to algae. Continuous-flow processing systems have been demonstrated for HTL of biomass. HTL concentrates bioenergy by a high yield of biocrude product. Biocrude can be catalytically hydrotreated to liquid hydrocarbon fuel components. The byproduct aqueous stream can be processed by CHG to maximize energy efficiency. Abstract: This review describes the recent results in hydrothermal liquefaction (HTL) of biomass in continuous-flow processing systems. Although much has been published about batch reactor tests of biomass HTL, there is only limited information yet available on continuous-flow tests, which can provide a more reasonable basis for process design and scale-up for commercialization. High-moisture biomass feedstocks are the most likely to be used in HTL. These materials are described and results of their processing are discussed. Engineered systems for HTL are described; however, they are of limited size and do not yet approach a demonstration scale of operation. With the results available, process models have been developed, and mass and energy balances determined. From these models, process costs have been calculated and provide some optimism as to the commercial likelihood of the technology.